Dermatoglyphic Patterns Among Undergraduate Students of a Medical College: A Descriptive Cross-sectional Study - Sintakala, Chandan; Manandhar, Prabina; Pandey, Niraj (Journal of Lumbini Medical College, 2020)
Introduction: Dermatoglyphics is the science that deals with the study of dermal ridge patterns on the digits, palms and soles as a whole. The present study is based on fingerprints related with the dermatoglyphic patterns of digits of hands. Apart from individual identification in institutions, it is also useful in forensic investigations to identify the criminals or dead bodies in accidental cases. This study aimed to find out the fingerprint patterns in right and left hands of undergraduate medical students. Methods: The study was performed in 200 students (97 males and 103 females) from first and second years of MBBS and B.Sc. nursing streams. The fingerprints were collected individually by pressing each of the finger tips on the stamp pad and then pressing it on A4 sized plain paper until the best finger print was observed. Results: Out of 2000 fingerprints, 1218(60.9%) were loops, 581 (29.05%) were whorls, 134(6.7%) were arches, and 67(3.35%) were composites. In males, there were 620 loops, 226 whorls, 98 arches and 26 composites whereas 602 loops, 351 whorls, 36 arches and 41 composites were found in females. Conclusion:The loop patterns were more common than other fingerprint patterns. Comparatively arches and loops were more common in males and whorls and composites in female.